2012
DOI: 10.1021/jp210988k
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Control Product Yield in Charge Separation Reaction from Second Excited State in Zinc–Porphyrin Derivatives?

Abstract: Intramolecular charge separation from the second singlet excited state of directly linked Zn-porphyrin-imide dyads and following charge recombination into the first singlet excited state has been investigated in the framework of a model involving three electronic states (the first and the second singlet excited and charge separated states) as well as their vibrational sublevels. Kinetics of the transitions between these states are described in terms of the stochastic point-transition approach. The influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 53 publications
(136 reference statements)
6
28
0
1
Order By: Relevance
“…However, a contribution of the CS state to this feature cannot be excluded. Such ultrafast CS and CR to a locally electronic excited state has already been observed with a ZnP containing dyad, 88,89 as well as in the bimolecular quenching of molecules in an upper electronic excited state. 49,90 The net result of this process in the arrays would be the same as the L Q -S 1 internal conversion.…”
Section: Cs In Toluene?supporting
confidence: 56%
“…However, a contribution of the CS state to this feature cannot be excluded. Such ultrafast CS and CR to a locally electronic excited state has already been observed with a ZnP containing dyad, 88,89 as well as in the bimolecular quenching of molecules in an upper electronic excited state. 49,90 The net result of this process in the arrays would be the same as the L Q -S 1 internal conversion.…”
Section: Cs In Toluene?supporting
confidence: 56%
“…Nonequilibrium transitions can be very effective because of the large number of excited vibrational states in polyatomic molecules so that only a small fraction of the particles on the U 2 term can avoid nonequilibrium transitions. 49,62 In this case, the product formation is expected to have a single stage and the decay of the excited state is nearly exponential (the rate constant weakly dependents on time). The effectiveness of nonequilibrium transitions strongly depends on the characteristics of the solvent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In a series of works, it was shown that PCET kinetics can be successfully described in terms of nonadiabatic transitions between several diabatic states. ,, The approach ,, is exploited here to simulate the kinetics of the coupled proton/electron transfer in I and II systems (which are denoted as PE). The multichannel stochastic approach which had previously been successfully applied for multistage ET kinetics simulation in donor–acceptor complexes and dyads is used in this work. ,,, It takes into account the solvent relaxation dynamics and reorganization of intramolecular high-frequency oscillations of PE and is well suited for ultrafast nonequilibrium kinetics modeling. For PCET kinetics description, three electronic states of the PE system are considered as follows: a ground state, PE, an electronically excited state, PE*, and a final product state, PCET*.…”
Section: Theory and Computational Detailsmentioning
confidence: 99%
“…Полученный ранее полуколичественный фитинг кинетики населенности состояния c разделенными зарядами (CS) для Zn(II)-порфирина, ковалентно связанного с нафталинимидом в DMF [18], был улучшен благодаря использованию более реальной модели с десятью высокочастотными колебательными модами. Рассчитанная кинетика населенности состояния CS количественно воспроизводит все особенности кинетики, наблюдаемой в эксперименте.…”
Section: заключениеunclassified